Functionally matched domains in parietal-frontal cortex of monkeys project to overlapping regions of the striatum. (December 2020) - Stepniewska, I; Pirkle, SC; Roy, T; Kaas, JH
Highlights: M1, PMC and PPC action-specific domains project mainly to the ipsilateral putamen. Corticostriatal pathways from functionally non-matching domains are segregated. Corticostriatal pathways from functionally matching domains substantially overlap. Arrangement of functionally distinct domains in putamen matches those of cortex. A cortico-basal ganglia circuit likely exists for each parietal-frontal network. Abstract: Projections of small regions (domains) of primary motor cortex (M1), premotor cortex (PMC) and posterior parietal cortex (PPC) to the striatum of squirrel monkeys were revealed by restricted injections of anterograde tracers. As many as 8 classes of action-specific domains can be identified in PPC, as well as in PMC and M1, and some have been identified for injections by the action evoked by 0.5 s trains of electrical microstimulation. Injections of domains in all three cortical regions labeled dense patches of terminations in the matrix of the ipsilateral putamen, while providing sparse or no projections to corresponding regions of the contralateral putamen. When two or three of these domains were injected with different tracers, projection fields in the putamen were highly overlapped for injections in functionally matched domains across cortical areas, but were highly segregated for injections placed in functionally mismatched domains. While not all classes of domains were studied, the results suggest that the striatum potentially has separate representations of eight or more classes of actions that receive inputs from domains in three or more cortical regions in sensorimotor cortex. The overlap/segregation of cortico-striatal projections correlates with the strength of cortico-cortical connections between injected motor areas.